Analisis Penggunaan Model Pembelajaran Discovery Learning pada Pembelajaran Pendidikan Agama Kristen dalam Memotivasi Kemampuan Berpikir Kritis Kelas XI di SMA Negeri 6 Palangka Raya - Yolan Gusta Pean (Pengharapan : Jurnal Pendidikan dan Pemuridan Kristen dan Katolik, 2026)
This study aims to analyze the application of the discovery learning model in motivating students' critical thinking skills in Christian Religious Education (PAK) class XI learning at SMA Negeri 6 Palangka Raya and identify its driving and inhibiting factors. The research method uses a descriptive qualitative approach with data collection techniques through observation, interviews, and documentation, with PAK teachers as the main subject. The analysis is carried out based on six stages of discovery learning, namely stimulation, problem identification, data collection, data processing, verification, and generalization, which are associated with critical thinking indicators. The results of the study show that the application of discovery learning makes a positive contribution to student engagement and the development of critical thinking skills. Students are active in identifying problems, collecting and processing information, presenting findings, providing responses, and drawing conclusions that can be accounted for. Motivating factors include intrinsic motivation, curiosity, teacher support, and the relevance of the material to daily life. Inhibiting factors include limited preparation time, lack of support resources, and difficulties for some students in following an exploratory approach. These obstacles can be overcome through careful planning, provision of supporting materials, and additional guidance. These findings confirm that discovery learning is an alternative to the PAK learning model that is active, student-centered, and effective in encouraging critical thinking skills.